2021
DOI: 10.1371/journal.pone.0257002
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Spanish hospital staff towards COVID-19 vaccination and vaccination rates

Abstract: Background COVID-19 vaccine hesitancy seems to be universal across countries and subgroups, and so are its determinants. We studied the willingness and factors associated with the decision to be vaccinated against COVID-19 in healthcare workers (HCW) in a Spanish tertiary hospital. Furthermore, we compared the percentage of willingness to vaccinate against COVID with actual vaccination rates among HCW in our hospital. Methods From December 21, 2020 to January 4, 2021, before initiation of the COVID-19 HCW va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…The seasonal influenza vaccination of PHCC personnel was one of the predictors for COVID-19 vaccination acceptance. Our results are in line with several similar studies where a strong correlation was observed [ 11 , 27 , 28 , 33 , 34 , 42 , 43 , 44 , 45 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…The seasonal influenza vaccination of PHCC personnel was one of the predictors for COVID-19 vaccination acceptance. Our results are in line with several similar studies where a strong correlation was observed [ 11 , 27 , 28 , 33 , 34 , 42 , 43 , 44 , 45 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…The study results expose the main underlying factor, which is a low level of fear of getting ill with the flu and its health complications, both for the given person and for other people potentially infected by this person. This renders the given person’s opinions and beliefs concerning vaccinations, and their earlier experiences with vaccinations, as dominating factors that determine their final decision concerning flu vaccination, and this is consistent with findings documented in other studies [ 6 , 8 , 18 , 22 ]. It successfully impregnates the person against any information—or observation-based persuasion—by relatives, family, acquaintances, the clergy, philosophers, journals, press, radio, television, the Internet or social media—which were only marginally mentioned by the participants of the study.…”
Section: Discussionsupporting
confidence: 90%
“…Among the factors increasing vaccine acceptance are trust in the vaccine and the belief that it is effective [ 9 ]; the perceived susceptibility and known severity of COVID-19 [ 10 ]; high level of vaccine literacy [ 7 ]; the will to prevent the spread of the disease [ 8 , 9 ]; the will to protect family members [ 8 ] or individuals with weak immune systems; the fact that everyone else around them is already vaccinated and being male and of older age [ 6 , 7 , 8 , 9 , 18 , 19 ]; high levels of confidence, having the feeling of a collective responsibility [ 9 ]; worrying about COVID-19 and being confident about the way the epidemic is being managed [ 19 ]; a higher level of education [ 7 ] (doctoral or Master’s degree, higher educational levels, or basic science laboratory workers) [ 20 ], especially being a physician [ 6 , 8 , 18 ]; treating vaccination as a means to reduce social isolation [ 21 ]; reported influenza vaccination [ 6 , 22 ] of at least once during the last three seasons [ 8 , 18 ] or complete vaccination against hepatitis B [ 8 ]; in addition to having the impression of being privileged to receive the vaccine [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2022;25(2):80-85. (6) , que son precisamente el grupo más afectado por la persistencia de síntomas tras el COVID, fundamentalmente tras infecciones leves. El Long COVID o COVID persistente, esta entidad aún por definir, afecta a un 15% de los infectados, que muestran persistencia de síntomas de tipo sistémico y psiconeurocognitivo para los que no hay un tratamiento específico ni un pronóstico acerca de su cronicidad.…”
Section: Editorial Editorialunclassified